Examination of the attitudes of patients in preoperative period toward uncertainty and the factors affecting the uncertainty (Annals of Medical Research, 2021)
Aim: To examine the attitudes of patients in preoperative period toward uncertainty and the factors affecting the uncertainty. Materials and Methods: The study had a relational descriptive design. It was conducted in the surgery clinics of a university hospital in the southeast of Turkey from November 2019 to February 2020. The study sample consisted of 200 patients in preoperative period. Results: The average score of patients in preoperative period from the attitudes toward uncertainty scale was 49.04±14.81. The average age of patients included in the study sample was 49.17±16.96. 59.5% of patients were female, 43.5% of them had an education below graduate level and 84.5% of them had someone to help with home care. A statistically significant difference was detected between the average uncertainty score and age, having someone to help with home care, total number of hospitalizations, American society of anesthesiologists preoperative risk status prior to surgical intervention and presence of any chronic diseases (p.05).Conclusion: Study findings indicate that patients in preoperative period had moderate levels of uncertainty. It was found that the patient’s age, having someone to help with home care, total number of hospitalizations, American society of anesthesiologists preoperative risk status and chronic disease variables affected the uncertainty levels. In the light of these results, it is thought that patients should be approached individually by taking these variables into consideration and the quality of patient support and their coping levels should be assessed.